A high-strength and high-toughness heat-resistant aluminum alloy and a preparation method thereof

CN122466324BActive Publication Date: 2026-10-09JIANGSU XINGHUAN AUTOMOBILE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610978261.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-09
Estimated Expiration
2046-07-02

AI Technical Summary

Technical Problem

[0007]本发明要解决的技术问题是:针对现有技术中存在铝合金耐热疲劳能力和力学性能不足的问题,为此我们提出一种耐热疲劳高强高韧铝合金及其制备方法

Benefits of technology

[0033] (1) The high-strength and high-toughness aluminum alloy with heat fatigue resistance provided by the present invention is added to the Al-Zn-Mg-Cu alloy by means of primary activation of ceramic material, sol-gel coating of TiO2 and secondary activation, through spray deposition. This effectively solves the problems of interface reaction between silicon carbide ceramic particles and aluminum alloy matrix to form brittle Al4C3, poor interface wettability leading to uneven particle dispersion, and interface thermal fatigue degradation under long-term high temperature alternating conditions. This significantly improves the heat fatigue resistance and high temperature mechanical properties of aluminum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122466324B_ABST
    Figure CN122466324B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of metal matrix composite material preparation, and discloses a heat fatigue resistant high-strength high-toughness aluminum alloy and a preparation method thereof. The high-strength high-toughness aluminum alloy comprises the following components in a mass percentage: Zn: 5.0%-9.0%, Mg: 1.5%-3.0%, Cu: 1.0%-3.0%, modified SiC@TiO2 nano ceramic: 5.0%-8.0%, and the rest is Al and inevitable impurities; the modified SiC@TiO2 nano ceramic is prepared through primary activation, sol-gel coating of a TiO2 shell and secondary activation of SiC ceramic particles; and the high-strength high-toughness aluminum alloy is prepared through a spraying deposition method. Through primary activation, sol-gel coating of TiO2 and secondary activation of ceramic materials, the ceramic materials are added in the aluminum alloy in a spraying deposition mode, the problems of interface reaction between silicon carbide ceramic particles and the aluminum alloy matrix to generate brittle Al4C3, poor interface wettability to cause uneven particle dispersion and interface thermal fatigue degradation under long-term high-temperature alternating working conditions are effectively solved, and the heat fatigue resistance and high-temperature mechanical properties of the aluminum alloy are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal matrix composite material preparation technology, and in particular to a heat-resistant, fatigue-resistant, high-strength, and high-toughness aluminum alloy and its preparation method. Background Technology

[0002] From an industry trend perspective, the development of lightweight and high-performance vehicles is accelerating, and heat-resistant aluminum alloys have become the core R&D direction for wheel manufacturing. In order to meet the industry's needs for technological upgrading and energy conservation and emission reduction, the limitations of existing materials can be broken through by independently developing exclusive heat-resistant materials.

[0003] Al-Zn-Mg-Cu alloys, as a class of heat-treatable ultra-high-strength aluminum alloys, traditionally occupy a core position in aerospace structural components through forgings or castings. However, existing aluminum alloys suffer from insufficient thermal fatigue resistance, making them prone to deformation and even cracking under long-term high-temperature alternating conditions. Furthermore, their mechanical properties degrade significantly at high temperatures, making them unsuitable for the stringent operating requirements of high-end vehicles. Repeated thermal stress can also accelerate wheel aging and damage. Therefore, improving the thermal fatigue resistance of aluminum alloys can effectively reduce wear and tear, lower after-sales maintenance costs, and enhance product durability.

[0004] Spray deposition, a metal forming process that combines rapid solidification and near-net-shape forming advantages, can effectively refine grains, increase the solid solubility of alloying elements, and suppress macroscopic segregation, making it particularly suitable for preparing high-performance particle-reinforced aluminum matrix composites. In the spray deposition process, ceramic reinforcing particles are injected into an atomizing cone and co-deposited with molten aluminum alloy droplets, achieving uniform dispersion and good interfacial bonding of the reinforcement. This provides an ideal process path for preparing high-strength, high-toughness aluminum alloy wheels with high resistance to thermal fatigue.

[0005] Silicon carbide ceramic particles are considered an ideal reinforcement for reducing thermal stress and improving thermal fatigue resistance in aluminum matrix composites due to their advantages such as low density, high elastic modulus, and extremely low coefficient of thermal expansion. However, in the existing process of reinforcing aluminum alloys with SiC ceramic particles, SiC and molten aluminum are thermodynamically unstable and easily react to form brittle needle-like Al4C3 phase, which severely damages the matrix and reduces mechanical properties, failing to effectively improve the thermal fatigue resistance of aluminum alloys.

[0006] Therefore, there is an urgent need for a high-strength, high-toughness aluminum alloy that can solve the compatibility problem between silicon carbide ceramic particles and aluminum alloys, and thus achieve both high thermal fatigue resistance and strong mechanical properties, as well as its preparation method. Summary of the Invention

[0007] The technical problem to be solved by this invention is: addressing the insufficient thermal fatigue resistance and mechanical properties of aluminum alloys in the prior art, we propose a high-strength and high-toughness aluminum alloy with thermal fatigue resistance and its preparation method.

[0008] To achieve the above objectives, this application adopts the following technical solution: a heat-resistant, fatigue-resistant, high-strength, and high-toughness aluminum alloy, wherein the mass percentage of each component in the high-strength, high-toughness aluminum alloy is Zn: 5.0%-9.0%, Mg: 1.5%-3.0%, Cu: 1.0%-3.0%, modified SiC@TiO2 nano-ceramics: 5.0%-8.0%, and the remainder is Al and unavoidable impurities;

[0009] The modified SiC@TiO2 nanoceramics are prepared by first activating SiC ceramic particles, coating TiO2 with a sol-gel layer, and then activating them again.

[0010] The high-strength and high-toughness aluminum alloy was prepared by spray deposition.

[0011] The high-strength and high-toughness aluminum alloy of the present invention contains at least 5% modified SiC@TiO2 nano-ceramic material and belongs to non-ferrous metal alloy.

[0012] Preferably, the Zn is added in the form of pure Zn, Mg and Cu are added in the form of Al-50Mg master alloy and Al-50Cu master alloy, respectively, and the remaining Al is added in the form of pure Al; the average particle size of the modified SiC@TiO2 nanoceramic is 5-30 μm.

[0013] Preferably, the modified SiC@TiO2 nanoceramics are prepared by the following steps:

[0014] (1) Place silicon carbide ceramic particles in hydrofluoric acid and sonicate for 1-3 minutes. After washing, immerse them in K2ZrF6 aqueous solution for 5-30 minutes. After washing and drying, obtain primary activated silicon carbide.

[0015] (2) After mixing tetrabutyl titanate, diethanolamine and anhydrous ethanol evenly, the pH was adjusted to 2-4 with dilute nitric acid to obtain TiO2 sol. Then, the activated silicon carbide was dispersed in TiO2 sol, stirred and aged, dried, and then calcined at 450-550℃ under nitrogen protection to obtain SiC@TiO2 powder.

[0016] (3) After SiC@TiO2 powder is subjected to physical bombardment and chemical grafting by Ar plasma and Ar / O2 mixed gas in sequence, it is immersed in K2TiF6 aqueous solution, stirred for 10-60 seconds, filtered and vacuum dried to obtain the modified SiC@TiO2 nanoceramics.

[0017] Preferably, in step (1), the mass concentration of hydrofluoric acid is 1%-5%; the mass concentration of the K2ZrF6 aqueous solution is 0.1%-0.5%; and the mass ratio of silicon carbide ceramic particles to K2ZrF6 is 1:0.001-0.01.

[0018] Preferably, in step (2), the mass ratio of SiC to TiO2 in the SiC@TiO2 powder is 1:0.02-0.1.

[0019] This invention effectively reduces the concentration of interfacial thermal stress between the reinforcement and the matrix by coating the surface of silicon carbide ceramic particles with a TiO2 layer, taking advantage of the good wettability of TiO2 with molten aluminum and the gradient transition of the coefficient of thermal expansion between TiO2 and SiC, thus significantly improving the thermal fatigue resistance and mechanical properties of aluminum alloys.

[0020] Preferably, the TiO2 sol also contains Ce(NO3)3, and the amount of Ce(NO3)3 added is 0.3%-1.5% of the mass of TiO2.

[0021] This invention stabilizes the crystal structure of the TiO2 shell by doping it with Ce, suppresses phase transformation and grain coarsening at high temperatures, and enables the shell to maintain its integrity and barrier function during high-temperature jet deposition and subsequent thermal cycling. This delays the interface aging and cracking process at high temperatures and further improves the thermal fatigue resistance of aluminum alloys.

[0022] Preferably, in step (3), the mass ratio of SiC@TiO2 to K2TiF6 is 1:0.0005-0.005; and the mass concentration of the K2TiF6 aqueous solution is 0.1%-0.5%.

[0023] The physical bombardment conditions are as follows: Ar plasma is introduced, gas flow rate is 20-50 sccm, processing power is 50-200W, working gas pressure is 10-50Pa, and processing time is 30-90s.

[0024] The chemical grafting conditions are as follows: an Ar / O2 mixed gas is introduced, the gas flow rate is 5-20 sccm, the processing power is 50-150W, the working gas pressure is 10-50Pa, and the processing time is 30-90s. In the Ar / O2 mixed gas, the volume ratio of Ar to O2 is 1-4:1.

[0025] The present invention also provides a method for preparing any of the above-mentioned heat fatigue resistant, high-strength, and high-toughness aluminum alloys, comprising the following steps:

[0026] (1) Weigh out pure Zn, Al-50Mg master alloy, Al-50Cu master alloy, pure Al and modified SiC@TiO2 nano-ceramics according to the proportion;

[0027] (2) Pure Zn, Al-50Mg, Al-50Cu and pure Al are melted into aluminum alloy melt, and atomized and sprayed under nitrogen protection. At the same time, modified SiC@TiO2 nano-ceramics are injected into the atomizing cone through a powder feeder with nitrogen as the carrier, and deposited together to obtain a billet.

[0028] (3) The billet is subjected to hot isostatic pressing densification treatment and then forged to obtain the heat fatigue resistant high strength and high toughness aluminum alloy.

[0029] This invention introduces modified SiC@TiO2 nano-ceramic particles uniformly into an Al-Zn-Mg-Cu alloy matrix via spray deposition. The high cooling rate of spray deposition further suppresses harmful interfacial reactions. At the same time, spray deposition can refine the matrix grains and increase the solid solubility of alloying elements, giving the material both excellent room temperature strength and toughness and high temperature thermal fatigue resistance, which can meet the stringent service requirements of high-end automotive wheel hubs under long-term braking high-temperature alternating conditions.

[0030] Preferably, in step (2), the temperature of the aluminum alloy melt is 700-800℃, the atomizing gas pressure is 0.5-2MPa, and the deposition distance is 300-600mm.

[0031] Preferably, in step (3), the temperature of hot isostatic pressing is 450-500℃, the pressure is 100-200MPa, and the time is 2-4 hours.

[0032] The technical effects and advantages of this invention are as follows:

[0033] (1) The high-strength and high-toughness aluminum alloy with heat fatigue resistance provided by the present invention is added to the Al-Zn-Mg-Cu alloy by means of primary activation of ceramic material, sol-gel coating of TiO2 and secondary activation, through spray deposition. This effectively solves the problems of interface reaction between silicon carbide ceramic particles and aluminum alloy matrix to form brittle Al4C3, poor interface wettability leading to uneven particle dispersion, and interface thermal fatigue degradation under long-term high temperature alternating conditions. This significantly improves the heat fatigue resistance and high temperature mechanical properties of aluminum alloy.

[0034] (2) The high-strength and high-toughness aluminum alloy with heat fatigue resistance provided by the present invention effectively reduces the interface thermal stress concentration between the reinforcement and the matrix by coating the surface of silicon carbide ceramic particles with TiO2 layer, utilizing the good wettability of TiO2 with aluminum liquid and the gradient transition of thermal expansion coefficient between TiO2 and SiC, and significantly improves the heat fatigue resistance and mechanical properties of aluminum alloy.

[0035] (3) The high-strength and high-toughness aluminum alloy with heat fatigue resistance provided by the present invention can stabilize the shell crystal structure and suppress phase transformation and grain coarsening at high temperature by doping Ce element in TiO2 shell, so that the shell can maintain its integrity and barrier function for a long time during high temperature flight of jet deposition and subsequent thermal cycling, delaying the interface aging and cracking process under high temperature conditions, and further improving the heat fatigue resistance of aluminum alloy.

[0036] (4) The high-strength and high-toughness aluminum alloy with heat fatigue resistance provided by the present invention is activated once before coating and immersed in K2ZrF6 aqueous solution, and Zr-F active anchor points are pre-placed on the SiC surface. This not only removes the inert SiO2 layer on the SiC surface, but also promotes the formation of Si-O-Zr chemical bridge bonds between SiC and TiO2 during subsequent TiO2 coating. The shell layer and the core are combined through chemical bonding, which significantly improves the adhesion and anti-stripping ability of the shell layer under high temperature impact and repeated thermal cycling of spray deposition, and further improves the heat fatigue resistance of the aluminum alloy.

[0037] (5) The high-strength and high-toughness aluminum alloy with heat fatigue resistance provided by the present invention is activated by Ar / O2 plasma physical bombardment and chemical grafting of SiC@TiO2 powder after coating, and immersed in K2TiF6 aqueous solution. A functionalized surface containing Ti-F active groups and high-density oxygen vacancies is constructed on the TiO2 shell surface. This surface triggers micro-aluminothermic reaction at the moment of contact with the aluminum alloy droplet, and generates nano-Al3Ti strengthening phase in situ, forming a gradient interface transition layer of metallurgical bonding. This not only achieves instantaneous complete wetting and uniform dispersion of the reinforcement and the aluminum liquid, but also effectively absorbs thermal cycling stress through the tough interface layer, significantly improving the high-temperature mechanical properties and heat fatigue resistance of the aluminum alloy.

[0038] (6) The high-strength and high-toughness aluminum alloy with heat fatigue resistance provided by the present invention introduces modified SiC@TiO2 nano-ceramic particles uniformly into the Al-Zn-Mg-Cu alloy matrix by spray deposition. The high cooling rate of spray deposition further suppresses harmful interfacial reactions. At the same time, spray deposition can refine the matrix grains and expand the solid solubility of alloying elements, so that the material has both excellent room temperature strength and toughness and high temperature heat fatigue resistance, which can meet the stringent service requirements of high-end automobile wheel hubs under long-term braking high temperature alternating conditions. Attached Figure Description

[0039] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention.

[0040] Figure 1 This is a flowchart illustrating the preparation process of the heat-resistant, fatigue-resistant, high-strength, and high-toughness aluminum alloy of this invention. Detailed Implementation

[0041] It is readily understood that, based on the technical solution of this invention, those skilled in the art can propose various interchangeable structural methods and implementations without altering the essential spirit of the invention. Therefore, the following detailed embodiments and accompanying drawings are merely illustrative examples of the technical solution of this invention and should not be considered as the entirety of the invention or as limitations or restrictions on the technical solution of this invention.

[0042] In a specific embodiment of the present invention, the silicon carbide ceramic particle raw material is high-purity ultrafine SiC powder with an average particle size of 5-30 μm and a purity of ≥99.5%; the CAS number of tetrabutyl titanate is 5593-70-4, analytical grade; the CAS number of diethanolamine is 111-42-2, analytical grade; and the remaining reagents and equipment are conventional reagents and equipment in this technical field.

[0043] Preparation of modified SiC@TiO2 nanoceramics-1

[0044] Modified SiC@TiO2 nanoceramics-1 were prepared by the following steps:

[0045] (1) In a polytetrafluoroethylene container equipped with an ultrasonic device, add 10g of SiC ceramic particles and 100mL of hydrofluoric acid with a mass concentration of 3%, sonicate for 2 minutes, immediately wash with a large amount of deionized water until neutral, then transfer the SiC particles to 150mL of K2ZrF6 aqueous solution with a mass concentration of 0.3%, soak for 15 minutes, take them out and wash them 3 times with deionized water, and vacuum dry them at 120℃ for 2 hours to obtain one-time activated SiC particles, wherein the mass ratio of silicon carbide ceramic particles to K2ZrF6 is 1:0.005;

[0046] (2) In a 250 mL three-necked flask equipped with a stirrer, add 0.05 mol of tetrabutyl titanate, 0.05 mol of diethanolamine and 150 mL of anhydrous ethanol, stir for 30 minutes, adjust the pH to 3.0 with dilute nitric acid to obtain TiO2 sol, disperse 10 g of once activated SiC particles in 50 mL of anhydrous ethanol by ultrasonication, slowly add to TiO2 sol, stir and react at 50 °C for 4 hours, age for 6 hours, filter, wash with ethanol 3 times, vacuum dry at 80 °C for 4 hours, then heat to 500 °C at 3 °C / min in a tube furnace under nitrogen protection, hold for 2 hours, cool with the furnace to obtain SiC@TiO2 powder, wherein the mass ratio of SiC to TiO2 is 1:0.05;

[0047] (3) Place 5g of SiC@TiO2 powder on the rotating sample stage of the plasma treatment chamber and rotate it at a constant speed of 10rpm. First, introduce pure Ar plasma with a flow rate of 30sccm, a treatment power of 100W, a working pressure of 30Pa, and a treatment time of 60 seconds for physical bombardment. Then switch to Ar / O2 mixed gas with a volume ratio of Ar to O2 of 3:1, a flow rate of 10sccm, a treatment power of 80W, a working pressure of 30Pa, and a treatment time of 60 seconds for chemical grafting. After plasma treatment, immediately immerse the powder in 100mL of K2TiF6 aqueous solution with a mass concentration of 0.3%, stir for 30 seconds, filter, and vacuum dry at 80℃ for 2 hours to obtain the modified SiC@TiO2 nanoceramic-1, wherein the mass ratio of SiC@TiO2 to K2TiF6 is 1:0.003.

[0048] Preparation of modified SiC@TiO2 nanoceramics-2

[0049] The preparation of the modified SiC@TiO2 nano-ceramics-1 is basically the same, except that Ce(NO3)3 is added to the TiO2 sol in step (2), and the amount of Ce(NO3)3 added is 0.8% of the mass of TiO2.

[0050] Preparation of modified SiC@TiO2 nanoceramics-3

[0051] The preparation of modified SiC@TiO2 nano-ceramics-1 is basically the same, except that step (1) is skipped and steps (2) and (3) are performed directly.

[0052] Preparation of modified SiC@TiO2 nanoceramics-4

[0053] The preparation of modified SiC@TiO2 nano-ceramics-1 is basically the same, except that step (3) is not performed, only steps (1) and (2) are performed.

[0054] Preparation of modified SiC@TiO2 nanoceramics-5

[0055] The preparation of modified SiC@TiO2 nano-ceramics-1 is basically the same, except that in step (3), the K2TiF6 aqueous solution is replaced with K2ZrF6 aqueous solution of equal mass concentration.

[0056] Example 1

[0057] The following steps are used to prepare a high-strength, high-toughness aluminum alloy resistant to thermal fatigue:

[0058] The ingredients were prepared according to the following mass percentages: Zn: 7.0%, Mg: 2.2%, Cu: 1.8%, modified SiC@TiO2 nano-ceramics-1: 5.0%, with the remainder being Al and unavoidable impurities.

[0059] (1) Weigh out pure Zn ingot, Al-50Mg master alloy, Al-50Cu master alloy, pure Al ingot and modified SiC@TiO2 nano-ceramic-1 powder according to the proportion;

[0060] (2) Pure Zn ingot, Al-50Mg master alloy, Al-50Cu master alloy and pure Al ingot are placed in a graphite crucible and heated to 760°C in a resistance furnace to melt into an aluminum alloy melt. Then, under nitrogen protection, the melt is atomized and sprayed. The atomizing gas pressure is 1.0 MPa, the aluminum alloy melt temperature is 760°C, and the deposition distance is 450 mm. At the same time, the modified SiC@TiO2 nano-ceramic-1 powder is injected into the atomizing cone through a powder feeder with nitrogen as the carrier, and deposited together with the aluminum alloy droplets to obtain a billet.

[0061] (3) The billet is subjected to hot isostatic pressing densification at a temperature of 470°C and a pressure of 150 MPa for 3 hours, and then forged to obtain the heat-resistant, fatigue-resistant, high-strength and high-toughness aluminum alloy.

[0062] Example 2

[0063] The method is basically the same as in Example 1, except that the Zn content is changed to 6.0%, the Mg content is changed to 2.0%, the Cu content is changed to 1.5%, and the modified SiC@TiO2 nano-ceramic-1 content is changed to 8.0%.

[0064] Example 3

[0065] The process is basically the same as in Example 1, except that modified SiC@TiO2 nanoceramics-1 is replaced with an equal amount of modified SiC@TiO2 nanoceramics-2.

[0066] Comparative Example 1

[0067] The basic formula is the same as in Example 1, except that modified SiC@TiO2 nanoceramics-1 are not added.

[0068] Comparative Example 2

[0069] The process is basically the same as in Example 1, except that the modified SiC@TiO2 nanoceramics-1 is replaced with an equal amount of SiC ceramic particles with an average particle size of 15μm.

[0070] Comparative Example 3

[0071] The process is basically the same as in Example 1, except that the modified SiC@TiO2 nanoceramics-1 is replaced with an equal amount of TiC ceramic particles with an average particle size of 15μm.

[0072] Comparative Example 4

[0073] The process is basically the same as in Example 1, except that the modified SiC@TiO2 nanoceramics-1 is replaced with an equal amount of modified SiC@TiO2 nanoceramics-3.

[0074] Comparative Example 5

[0075] The process is basically the same as in Example 1, except that the modified SiC@TiO2 nanoceramics-1 is replaced with an equal amount of modified SiC@TiO2 nanoceramics-4.

[0076] Comparative Example 6

[0077] The process is basically the same as in Example 1, except that the modified SiC@TiO2 nanoceramics-1 is replaced with an equal amount of modified SiC@TiO2 nanoceramics-5.

[0078] Performance testing:

[0079] 1. Room temperature mechanical property test: According to the test standard GB / T 228.1-2021, the tensile strength-1 and yield strength-1 were tested using a universal testing machine at a tensile rate of 2 mm / min.

[0080] The test results are shown in Table 1 below:

[0081] Table 1

[0082] Tensile strength - 1 (MPa) Yield strength - 1 (MPa) Example 1 635 562 Example 2 612 548 Example 3 641 568 Comparative Example 1 562 515 Comparative Example 2 583 532 Comparative Example 3 622 556 Comparative Example 4 598 538 Comparative Example 5 605 542 Comparative Example 6 615 550

[0083] 2. High-temperature mechanical property test: According to the test standard of GB / T 228.2-2015, the tensile strength-2 and yield strength-2 were tested after being kept at 300℃ for 15 minutes, and the tensile rate was 1mm / min.

[0084] 3. Thermal fatigue performance test: The test was conducted using a self-restrained thermal fatigue testing machine. The specimens were subjected to cyclic heating and cooling between room temperature and 350℃. Each cycle consisted of heating to 350℃ and holding for 30 seconds, followed by forced cooling to room temperature with compressed air and holding for 30 seconds. A complete cycle lasted 60 seconds. After 5000 thermal cycles, the surface fatigue crack morphology was observed using a metallographic microscope. The maximum crack length was measured, and the number of cycles when a crack with a length ≥ 0.5 mm appeared was recorded as the thermal fatigue life. Five specimens were tested in each group, and the average value was taken.

[0085] The test results are shown in Table 2 below:

[0086] Table 2

[0087] Tensile strength - 2 (MPa) Yield strength - 2 (MPa) Crack length (mm) Loop count Example 1 342 315 0.18 4850 Example 2 326 302 0.22 4620 Example 3 348 320 0.16 4920 Comparative Example 1 218 195 0.68 2150 Comparative Example 2 245 218 0.75 1850 Comparative Example 3 328 304 0.28 4520 Comparative Example 4 278 251 0.45 3680 Comparative Example 5 305 282 0.35 4120 Comparative Example 6 332 308 0.24 4650

[0088] According to the test results of Examples 1-3, the high-strength and high-toughness aluminum alloy with thermal fatigue resistance provided by the present invention achieves excellent mechanical properties and thermal fatigue resistance by adding modified SiC@TiO2 nano-ceramic particles to the Al-Zn-Mg-Cu alloy matrix. At the same time, according to the test results of Example 3, when Ce element is introduced into the modified SiC@TiO2 nano-ceramic to dope and modify the TiO2 shell, the overall performance can be further improved.

[0089] The test results of Examples 1-3 and Comparative Examples 1-3 show that the present invention, by adding multi-level modified SiC@TiO2 nano-ceramic particles to aluminum alloy, has significant advantages over untreated SiC and TiC in reducing thermal stress and improving thermal fatigue resistance.

[0090] Based on the comparison of the test results of Examples 1-3 and Comparative Examples 4-6, it can be seen that the present invention forms a multi-layer gradient interface structure by first activating and dipping SiC ceramics with K2ZrF6 to construct Si-O-Zr anchor points, coating TiO2 shell with sol-gel, and second activating and dipping with K2TiF6 to construct Ti-F active surface. This structure can be added to Al-Zn-Mg-Cu alloys by spray deposition, which significantly improves the thermal fatigue resistance and high-temperature mechanical properties of aluminum alloys.

[0091] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.

Claims

1. A high-strength, high-toughness aluminum alloy resistant to heat fatigue, characterized in that, The high-strength and high-toughness aluminum alloy contains the following components by mass percentage: Zn: 5.0%-9.0%, Mg: 1.5%-3.0%, Cu: 1.0%-3.0%, modified SiC@TiO2 nano-ceramics: 5.0%-8.0%, with the remainder being Al and unavoidable impurities. The modified SiC@TiO2 nanoceramics are prepared by first-stage activation of SiC ceramic particles, sol-gel coating of TiO2 shell, and second-stage activation. The high-strength and high-toughness aluminum alloy was prepared by spray deposition. The modified SiC@TiO2 nanoceramics were prepared through the following steps: (1) Place silicon carbide ceramic particles in hydrofluoric acid and sonicate for 1-3 minutes. After washing, immerse them in K2ZrF6 aqueous solution for 5-30 minutes. After washing and drying, obtain primary activated silicon carbide. (2) After mixing tetrabutyl titanate, diethanolamine and anhydrous ethanol evenly, the pH was adjusted to 2-4 with dilute nitric acid to obtain TiO2 sol. Then, the activated silicon carbide was dispersed in TiO2 sol, stirred and aged, dried, and then calcined at 450-550℃ under nitrogen protection to obtain SiC@TiO2 powder. (3) After SiC@TiO2 powder is subjected to physical bombardment and chemical grafting by Ar plasma and Ar / O2 mixed gas in sequence, it is immersed in K2TiF6 aqueous solution, stirred for 10-60 seconds, filtered and vacuum dried to obtain the modified SiC@TiO2 nano-ceramic; The modified SiC@TiO2 nanoceramics have an average particle size of 5-30 μm; In step (2), the mass ratio of SiC to TiO2 in the SiC@TiO2 powder is 1:0.02-0.

1.

2. The high-strength, high-toughness aluminum alloy resistant to heat fatigue according to claim 1, characterized in that, The Zn is added in the form of pure Zn, Mg and Cu are added in the form of Al-50Mg master alloy and Al-50Cu master alloy, respectively, and the remaining Al is added in the form of pure Al.

3. The high-strength, high-toughness aluminum alloy resistant to heat fatigue according to claim 1, characterized in that, In step (1), the mass concentration of hydrofluoric acid is 1%-5%; the mass concentration of the K2ZrF6 aqueous solution is 0.1%-0.5%; and the mass ratio of silicon carbide ceramic particles to K2ZrF6 is 1:0.001-0.

01.

4. The high-strength, high-toughness aluminum alloy resistant to heat fatigue according to claim 1, characterized in that, The TiO2 sol also contains Ce(NO3)3, and the amount of Ce(NO3)3 added is 0.3%-1.5% of the mass of TiO2.

5. The high-strength, high-toughness aluminum alloy resistant to heat fatigue according to claim 1, characterized in that, In step (3), the mass ratio of SiC@TiO2 to K2TiF6 is 1:0.0005-0.005; the mass concentration of the K2TiF6 aqueous solution is 0.1%-0.5%. The physical bombardment conditions are as follows: Ar plasma is introduced, gas flow rate is 20-50 sccm, processing power is 50-200W, working gas pressure is 10-50Pa, and processing time is 30-90s. The chemical grafting conditions are as follows: an Ar / O2 mixed gas is introduced, the gas flow rate is 5-20 sccm, the processing power is 50-150W, the working gas pressure is 10-50Pa, and the processing time is 30-90s. In the Ar / O2 mixed gas, the volume ratio of Ar to O2 is 1-4:

1.

6. The method for preparing the heat-fatigue resistant, high-strength, and high-toughness aluminum alloy according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Weigh out pure Zn, Al-50Mg master alloy, Al-50Cu master alloy, pure Al and modified SiC@TiO2 nano-ceramics according to the proportion; (2) Pure Zn, Al-50Mg, Al-50Cu and pure Al are melted into aluminum alloy melt, and atomized and sprayed under nitrogen protection. At the same time, modified SiC@TiO2 nano-ceramics are injected into the atomizing cone through a powder feeder with nitrogen as the carrier, and deposited together to obtain a billet. (3) The billet is subjected to hot isostatic pressing densification treatment and then forged to obtain the heat fatigue resistant high strength and high toughness aluminum alloy.

7. The method for preparing the heat-fatigue resistant, high-strength, and high-toughness aluminum alloy according to claim 6, characterized in that, In step (2), the temperature of the aluminum alloy melt is 700-800℃, the pressure of the atomizing gas is 0.5-2MPa, and the deposition distance is 300-600mm.

8. The method for preparing the heat-fatigue resistant, high-strength, and high-toughness aluminum alloy according to claim 6, characterized in that, In step (3), the temperature of hot isostatic pressing is 450-500℃, the pressure is 100-200MPa, and the time is 2-4 hours.

Citation Information

Patent Citations

  • Preparation method for SiC particle reinforced aluminum-based composite material

    CN103484707A

  • Die-casting aluminum alloy modified by carbide nanoparticles and preparation method thereof

    CN112662909A